2020
DOI: 10.1097/sla.0000000000004267
|View full text |Cite
|
Sign up to set email alerts
|

Defining Benchmark Outcomes for Pancreatoduodenectomy With Portomesenteric Venous Resection

Abstract: Objective: The aim of this study was to establish clinically relevant outcome benchmark values using criteria for pancreatoduodenectomy (PD) with portomesenteric venous resection (PVR) from a low-risk cohort managed in high-volume centers. Summary Background Data: PD with PVR is regarded as the standard of care in patients with cancer involvement of the portomesenteric venous axis. There are, however, no benchmark outcome indicators for this population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 30 publications
3
74
0
Order By: Relevance
“…Reporting of postoperative outcomes as textbook-or benchmark outcomes facilitates international comparison. 61,74,75 The present study has a few limitations: First of all, the heterogenous definitions of the learning curve make comparisons difficult. Therefore, this study is mainly a qualitative review presenting the available data in an attempt to standardize reporting of learning curves in pancreatic surgery.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Reporting of postoperative outcomes as textbook-or benchmark outcomes facilitates international comparison. 61,74,75 The present study has a few limitations: First of all, the heterogenous definitions of the learning curve make comparisons difficult. Therefore, this study is mainly a qualitative review presenting the available data in an attempt to standardize reporting of learning curves in pancreatic surgery.…”
Section: Discussionmentioning
confidence: 97%
“…In the initial learning period, surgeons usually select low-risk patients with favorable anatomical (low BMI) and disease specific features (cystic lesions, small tumors, no vessel involvement). 47 After accumulating experience, technically more challenging and more complex cases such as advanced tumors with vascular involvement [59][60][61] or initially irresectable tumors after neoadjuvant treatment 32,62 are selected and affect the learning curve in a later stage. 58,59 Miskovic et al suggested a case selection algorithm according to disease complexity in colorectal surgery, taking into account tumor size and inflammatory disease that increased the difficulty of the surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 18 ] However, partial venous resection, such as a portal vein, superior mesenteric vein, and splenic vein, are feasible, and several centers have been performing these procedures. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, an establishment of clinical databases from international centers with an accurate collection of demographic, management, and outcome data for respective surgical procedures is needed. The importance of establishing benchmarks has been demonstrated for various surgical procedures in general and visceral surgery (11)(12)(13)(14)(15). As yet, there is very little published about acceptable neurosurgical benchmarks.…”
Section: Introductionmentioning
confidence: 99%